METODOLOGI PROGRAM RISET IMRE LAKATOS - Ahmad Saka Falwa Guna; Fitria Ramadhani (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2021)
This research was based on the limitations of the human mind itself in providing and obtaining reasonable explanations, because at that time the desire to know something was obstructed from various myths which existedin that society so that myths were embedded in human mind. The focus of this research was on the methodology of the Imre Lakatos research program. The purpose of this study was to determine the process of research program methodology from Imre Lakatos. The method used in this research was library research, where the researchers looked for and read sources that match the title to be studied, such as books, articles, writings and journals that were relevant.The results of this study in the Imre Lakatos research program methodology included: First, the core (hardcore) functions as a negative heuristic. Second, the protective-belt which consisted of auxiliary hypotheses in the initial conditions. Third, a series of theories (a series theory), theory linkages where the next theory was the result of the auxiliary clauses added from the previous theory.